ENGLISH MEDIUM INSTRUCTION IN ASIAN UNIVERSITIES: SOME CONCERNS AND A SUGGESTED APPROACH TO DUAL-MEDIUM INSTRUCTION - Barnard, Roger (Indonesian Journal of Applied Linguistics, 2014)
Abstract: An increasing number of universities across the world are adopting English as the medium of instruction, particularly at the graduate level. This paper begins by briefly describing the historical development of such English medium instruction (EMI) programmes in European universities, and the reasons which are frequently given to justify them. A number of examples of EMI policies in Asian universities are provided to indicate the rapidly growing trend in this region. However, little attention appears to have been paid to some of the negative implications of adopting EMI programmes, and these concerns are articulated here. It is suggested that, instead of adopting strictly monolingual EMI programmes, university authorities should consider a principled approach to dual medium instruction. The value of combining English with the vernacular language is outlined, and a model for such a programme is presented and explained.Â Keywords: English medium instruction, dual- focused approach, content and language integrated learning